Strategic reading groups guiding readers in the middle grades - Berne, Jennifer
Strategic grouping can transform reading instruction in the middle grades from a hit-or-miss learning experience to a targeted, responsive one. This book features a practical and field-tested model for small-group differentiated reading instruction in Grades 4-8. Jennifer Berne and Sophie C. Degener offer a clear, detailed discussion of how to position this instruction inside middle school language arts or reading classrooms and simple, effective strategies for classroom management, groupings, and assessment
Keywords: Reading (Middle school); Group reading